Adeno-Associated Virus (AAV) Gene Delivery: Dissecting Molecular Interactions upon Cell Entry - Large, Edward E. (Viruses, 2021)
Human gene therapy has advanced from twentieth-century conception to twenty-first-century reality. The recombinant Adeno-Associated Virus (rAAV) is a major gene therapy vector. Research continues to improve rAAV safety and efficacy using a variety of AAV capsid modification strategies. Significant factors influencing rAAV transduction efficiency include neutralizing antibodies, attachment factor interactions and receptor binding. Advances in understanding the molecular interactions during rAAV cell entry combined with improved capsid modulation strategies will help guide the design and engineering of safer and more efficient rAAV gene therapy vectors.